Social Programs of Sweden : a Search for Security in a Free Society. - Rosenthal, Albert H. (University of Minnesota Press, 1967)
In his forward to this book, Marquis Childs, author of the classic work Sweden: The Middle Way, comments: "There has been a great deal of emotional writing about the effort of the labor government in Stockholm to regulate capitalism and provide a decent s.